Social Responsibility for Indonesian Migrant Workers' Children in Malaysia - Qomariyah, Lailatul; Umam, Muhammad Khairul; Abdullah, A. Fatikhul Amin (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2024)
The study is undermined by the educational conditions of children of Indonesian Migrant Workers (PMI) in Malaysia who can’t freely attend school. Because her parents don't have official documents and charges so the kids just shut up in the compartment. On the other hand, with a Sanggar named An-Nahdloh the children of PMI can access education easily. This research was carried out with the aim of: (1) Identifying the actual conditions related to the education of PMI children before joining Sanggar Guidance. (2) Describing the role of Sanggar guidance in accessing education for PMI kids in Malaysia. The method used is a qualitative method with a phenomenological approach. The data collection technique in this study is participation observation, interviews and documentation. Participation observations are combined with interviews to produce concrete and detailed data. The results of the research show that, in the presence of this guidance. Helping and making it easier for PMIs to access their children's education by joining the mentoring Sanggar. After joining the SB, the children of the PMI can read, write, and count. As well as the child's security in accessing education when returning to Indonesia, they can continue and have an official degree.